Licensing innovations: The case of the inside patent holder - Cuihong Fan; Byoung Heon Jun; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
The present paper reconsiders the inside innovators' licensing problem under incomplete information. Employing an optimal mechanism design approach, we show that, contrary to what is claimed in the literature, the optimal mechanism may prescribe fixed fees, royalty rates lower than the cost reduction, and even negative royalty rates.
urn:nbn:de:bvb:19-epub-24906-7
Keywords: D21; D43; D44; D45; 330; innovation; licensing; industrial organization